Institutional Capacity Building to Support the Livelihoods of Coffee Farmers in Horsik Village, Ajibata Subdistrict, Toba Samosir Regency, North Sumatra - Henry Sitorus; Hamdani Harahap (Journal of Oral Traditions, 2025)
Coffee has become a highly favored commodity among various communities. One of the coffee-producing areas in Ajibata Subdistrict is Horsik Village, where farmers cultivate coffee on the slopes of the Toba Caldera. This article explains the strategy of strengthening farmers' economic institutions, starting from traditional planting and cultivation of robusta coffee based on local knowledge transmission to increasing the value of coffee products through local and regional market integration. The traditional technologies used have resulted in low yield quality and quantity, which subsequently leads to insufficient income for the socio-economic needs of the community. Strengthening institutional capacity through knowledge transfer, skill development, and provision of tools and technology for post-harvest processing is essential to improve productivity, income, and overall economic well-being of coffee farmers.